Idosos dependentes e desacompanhados em pronto socorro público: os outros lados do abandono - Braga, Luciana de Souza (2010)
The lack of elderly care services in Brazil has made essential the further studies on opportunities and containment barriers of the worsen of social issues related to dependent and unaccompanied elderly trying to get protection from the Ready Public Aid, particularly considering the political framework that sets, with a state that is shown inoperative with recessive policies, and with scarce public services and resources for care and accommodation of the elderly in a situation of social vulnerability. We aim to portray the reality in a deep and complex way with all its determinants, through the access to different sources of information which can be appealed in order to demystify the idea that all elders can be cared by their families. This is a qualitative study in which we used the study of cases method, because it is a way to investigate reality according to some sources of evidence, sufficiently complex and rich in data, and also capable of examining the context in which the intervention took place, allowing to explore the set of results. Among the results it is noticed that the vision of the State tends to homogenize the elderly presupposing that all of them constituted families and that these families should and can take care of their elders